Ideological Constraints in Dubbing The Simpsons into Arabic (Altre Modernità, 2016)
Although Audiovisual Translation has received considerable attention in recent years, evidence suggests that there is a paucity of empirical research carried out on the topic of ideological constraints in audiovisual translation from English into Arabic. This is despite the fact that subtitling and dubbing Western animation into Arabic has been on the increase ever since television sets entered Arab homes; which is why several authority figures are calling for tighter control and moral screening of what is aired on television sets, in particular that which is aimed at children. This study aims to add some understanding of the problems facing practitioners in the dubbing industry, such as the reasons for their alleged reality distortion and how these problems are dealt with by the dubbing agencies. This is achieved by exploring the extent ideological norms, as well as other agents, shape the outcome of dubbed English animations/films when rendered into Arabic by manipulation, subversion and/or appropriation. Fifty-two dubbed episodes of The Simpsons were selected for this study. The Simpsons was chosen due to its universal appeal and influence. It addresses many sensitive issues, such as sex, drugs, religion, politics, racial and gender stereotypes, with a bluntness and boldness rarely seen before, and goes beyond passive entertainment and school education. Therefore, it is looked at with suspicion and vigilance in the Arab World. The contrastive analysis of the English and Arabic versions of The Simpsons yielded interesting results; it established that the translation process is marred by many intrinsic and extrinsic factors either exercised by the translator or imposed upon him. Ideological and socio-cultural factors are the chief culprits in the case of translating The Simpsons into Arabic.